Acoustic interaction of submerged thin-shell structures considering seabed reflection effects - Zhang, Xin; Ai, Kai; Yang, Sen; Pei, Qingxiang; Lei, Guang (Frontiers in Physics, 2025)
This paper presents a novel approach for simulating acoustic-shell interaction, specifically focusing on seabed reflection effects. The interaction between acoustic waves and shell vibration is crucial in various engineering applications, particularly in underwater acoustics and ocean engineering. The study employs the finite element method (FEM) with Kirchhoff-Love shell elements to numerically analyze thin-shell vibrations. The boundary element method (BEM) is applied to simulate exterior acoustic fields and seabed reflections, using half-space fundamental solutions. The FEM and BEM are coupled to model the interaction between acoustic waves and shell vibration. Furthermore, the FEM-BEM approach is implemented within an isogeometric analysis (IGA) framework, where the basis functions used for geometric modeling also discretize the physical fields. This ensures geometric exactness, eliminates meshing, and enables the use of Kirchhoff-Love shell theory with high-order continuous fields. The coupled FEM-BEM system is accelerated using the fast multipole method (FMM), which reduces computational time and memory storage. Numerical examples demonstrate the effectiveness and efficiency of the proposed algorithm in simulating acoustic-shell interaction with seabed reflection.